Significant impact of mTORC1 and ATF4 pathways in CHO cell recombinant protein production induced by CDK4/6 inhibitor. Issue 5 (17th February 2022) - Chang, Meiping; Huhn, Steven; Nelson, Luke; Betenbaugh, Michael; Du, Zhimei
Abstract: The CDK4/6 inhibitor has been shown to increase recombinant protein productivity in Chinese hamster ovary (CHO) cells. Therefore, we investigated the mechanism that couples cell‐cycle inhibitor (CCI) treatment with protein productivity utilizing proteomics and phosphoproteomics. We identified mTORC1 as a critical early signaling event that preceded boosted productivity. Following CCI treatment, mTOR exhibited a transient increase in phosphorylation at a novel site that is also conserved in humans and mouse. Upstream of mTORC1, increased phosphorylation of AKT1S1 and decreased phosphorylation of RB1 may provide molecular links between CDK4/6 inhibition and mTORC1. Downstream, increased EIF4EBP1 phosphorylation was observed, which can mediate cap‐dependent translation. In addition, the collective effect of increased phosphorylation of RPS6, increased phosphorylation of regulators of RNA polymerase I, and increased protein expression in the transfer RNA‐aminoacylation pathway may contribute to enhancing the translational apparatus for increased productivity. In concert, an elevated stress response via GCN2/EIF2AK4‐ATF4 axis persisted over the treatment course, which may link mTOR to downstream responses including the unfolded protein response and autophagy to enhance proper protein folding and secretion. Together, this comprehensive proteomics and phosphoproteomics characterization of CCI‐treated CHO cells offers insights into understanding multiple aspects of signaling events resulting from CDK4/CDK6 inhibition. Abstract : The development of efficient bioprocess strategies is critical for biotherapeutic production. The authors investigated the underlying mechanism of CDK4/6 inhibitor (cell‐cycle inhibitor [CCI])‐induced enhancement of recombinant protein productivity for clones derived from two different Chinese hamster ovary hosts. By performing phosphoproteomics and proteomics analysis, they identified signaling events and pathways and uncovered multiple lines of evidence supporting mTORC1 and ATF4 as early signaling events in the CCI treatment leading to the boosted productivity. A previously unidentified phosphorylation site on the mTOR sequence is highlighted.